Efficacy and safety of Chinese herbal medicine in post-stroke epilepsy: a systematic review and meta-analysis - Sun, Tianye; Wang, Kaiyue; Li, Lili; Yan, Mingyuan; Wu, Jing; Liu, Jinmin (Frontiers in Pharmacology, 2023)
Background: Poststroke epilepsy (PSE) is a common complication of strokes that seriously affects the recovery and quality of life of patients, and effective treatments are needed. Chinese herbal medicine (CHM) adjunctive therapy is a viable treatment option, but current evidence is insufficient to support its efficacy and safety. This study aimed to evaluate the efficacy and tolerability of CHM adjunctive therapy in the treatment of PSE. Methods: A systematic search of eight databases was conducted to identify PSE-related randomized clinical trials from the inception of each database through October 2023. The methodological quality assessment was conducted by RoB 2.0, meta-analysis was conducted by RevMan 5.3 and Stata 15.1, and evidence quality was evaluated by GRADE. Results: Twenty-three RCTs involving 1,901 PSE patients were identified. We found that orally administered CHM plus conventional Western medicine (CWM) was superior to CWM monotherapy in increasing the 75% responder rate (RR 1.46, 95% CI: 1.31 to 1.62, p < 0.00001), decreasing the seizure duration (MD -1.01, 95% CI: −1.30 to −0.72, p < 0.00001), improving total responder rate (RR 1.29, 95% CI: 1.20 to 1.37, p < 0.00001), reducing epileptiform discharges (EDs) (MD -2.02.46, 95% CI: −2.64 to −1.40, p < 0.00001), and decreasing the number of leads involved in epileptiform discharge (MD -3.92, 95% CI: −5.15 to −2.68, p < 0.00001). Furthermore, intravenously administered CHM plus CWM was superior regarding 75% responder rate (RR 1.39, 95% CI: 1.24 to 1.56, p < 0.00001), total responder rate (RR 1.29, 95% CI: 1.20 to 1.39, p < 0.00001), EDs (MD -3.92, 95% CI: −5.15 to −2.68, p < 0.00001), and the number of leads involved in epileptiform discharge (MD -1.82, 95% CI: −2.62 to −1.02, p < 0.00001). However, regarding the 50%–75% responder rate, there was no statistically significant difference between the two groups for either oral (RR 1.00, 95% CI: 0.77 to 1.29, p = 0.98) or injectable CHM (RR 0.95, 95% CI: 0.67 to 1.33, p = 0.75). Both orally administered CHM plus CWM (RR 0.56, 95% CI: 0.35 to 0.90, p = 0.02) and intravenously administered CHM plus CWM (RR 0.64, 95% CI: 0.45 to 0.90, p = 0.010) caused fewer AEs than CWM. Furthermore, the levels of evidence ranged from low to high due to publication bias and heterogeneity. Conclusion: CHM adjuvant therapy may be an effective and safe therapy for PSE. However, due to the poor quality of clinical data, more well-designed RCTs are needed to confirm these findings. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=364356, identifier PROSPERO (CRD42022364356)